Evaluation of Stackelberg Leader-Follower Interaction Between Policymakers in Small Open Economies - Tetik, Metin; Ceylan, Reşat (Ekonomika, 2021)
The problem of coordination between policymakers seems to have created fundamental problems related to economic and social costs, targeted inflation, potential growth, and a high budget deficit. To resolve these problems in this framework, it is important to see the results of the interaction between policymakers and to propose an optimal policy strategy. In this study, the interactions between monetary and fiscal policymakers are examined game theoretically within the framework of the New Keynesian model. The strategic interaction between these policymakers is assessed using the DSGE (Dynamic Stochastic General Equilibrium) model for a small open economy. From this point of view, the interaction between policymakers is assessed within the framework of hypothetical scenarios. The optimal monetary and fiscal policies for a small open economy are derived from the leader-follower mechanism solution known as the Stackelberg solution. Optimal Stackelberg policy rules derived for a small open economy contribute to the literature of economics. The performance of the game theoretically derived optimal policy rules is evaluated through dynamic simulation within the framework of counterfactual experiments. The parameters developed for the model are calibrated for the Turkish economy. Dynamic simulation of the models, the impulse response functions, and the social loss analysis shows that the optimal policy mix for the Turkish economy is when the monetary policymaker is the leader, and the fiscal policymaker is the follower.